STUDY OF PERSONNEL REACTION ON IMPLEMENTATION OF CORPORATE GOVERNANCE DIGITALIZATION PROGRAMS - A. V. Raychenko (Вестник университета)
The national digitalization program determines the radical transformation of information support and administrative support for the implementation of the functions and procedures of managers, specialists and executives of the management apparatus. The universally declared recognition of the necessity and prospects of the developed and ongoing innovations in information support and management processes does not exclude negative reactions of personnel to their implementation and possible consequences. The study of personnel reactions to the implementation of corporate governance digitalization programs, presented by this publication, demonstrates the methods, materials, and results of identifying, analysing, and evaluating sustainable staff responses to management digitalization. As a result of research in corporations that are actively involved in information innovations, the trends that should be taken into account to improve the effectiveness of digitalization programs have been highlighted.